2019
DOI: 10.1159/000504287
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes among Patients Treated with Renal Replacement Therapy during Extracorporeal Membrane Oxygenation: A Single-Center Retrospective Study

Abstract: Background: Extracorporeal membrane oxygenation (ECMO) and continuous renal replacement therapy (CRRT) are modalities used in critically ill patients suffering organ failure and metabolic derangements. Although the effects of CRRT have been extensively studied, the impact of simultaneous CRRT and ECMO is less well described. The purpose of this study is to evaluate the incidence and the impact of CRRT on outcomes of patients receiving ECMO. Methods: A single center, retrospective chart review was conducted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 27 publications
(50 reference statements)
2
26
0
1
Order By: Relevance
“…In total, 25 studies detailing 5896 adult patients that reported on the use of RRT and ECMO were included ( Table 1 ) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Twenty-four studies were observational in nature [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], while one study was a randomised controlled trial (RCT) [ 52 ]. For our quantitative analysis, we included 24 observational studies (5855 patients), while the findings of the RCT were reported separately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 25 studies detailing 5896 adult patients that reported on the use of RRT and ECMO were included ( Table 1 ) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Twenty-four studies were observational in nature [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], while one study was a randomised controlled trial (RCT) [ 52 ]. For our quantitative analysis, we included 24 observational studies (5855 patients), while the findings of the RCT were reported separately.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled overall mortality ( Figure 1 ) in patients due to the use of RRT on ECMO (24 studies) was 62.9% (95% CI: 56.0–69.6%). Subgroup analysis found no significant differences ( p = 0.57) between in-hospital mortality (14 studies, 60.1%, 95% CI: 50.1–69.8%) [ 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 42 , 43 , 45 , 48 , 49 , 50 ], ICU mortality (3 studies, 67.3%, 95% CI: 60.1–74.1%) [ 28 , 29 , 32 ], 30-day mortality (3 studies, 68.4%, 95% CI: 58.0–77.9%) [ 41 , 44 , 47 ], and 90-day mortality (3 studies, 57.0%, 95% CI: 17.6–92.0%) [ 30 , 40 , 46 ]. Only one study mentioned overall mortality [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fluid overload is usually secondary to AKI or improper volume management during ECMO treatment. Research has shown that 40–60% of patients on ECMO who developed AKI were placed on CRRT [ 29 ]. Another study from the Extracorporeal Life Support Organization found that the indications for ECMO combined with CRRT include fluid overload (43%), AKI (35%), prevention of fluid overload (16%), electrolyte imbalances (4%) and other complications (2%) [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…Another study from the Extracorporeal Life Support Organization found that the indications for ECMO combined with CRRT include fluid overload (43%), AKI (35%), prevention of fluid overload (16%), electrolyte imbalances (4%) and other complications (2%) [ 30 ]. Nevertheless, combined therapy was associated with increased mortality compared with ECMO alone, which ranged from 39.5% to 100% [ 29 , 31 , 32 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation